2022
DOI: 10.2147/clep.s344515
|View full text |Cite
|
Sign up to set email alerts
|

Positive Predictive Value of the ICD-10 Diagnosis Code for Long-COVID

Abstract: To examine the positive predictive value (PPV) of International Classification version 10 (ICD-10) diagnosis codes for long coronavirus disease 2019 (long-COVID) in a Danish Health registry. Patients and Methods: This was a medical record review of all patients with a diagnosis code of long-COVID (DB948A) at all hospitals in the North Denmark Region from February 27, 2020 through June 30, 2021. Confirmed long-COVID was categorized as fulfillment of all three criteria: (1) a positive polymerase chain reaction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Our study did not focus specifically on long COVID, but instead investigated a cohort of patients following a diagnosis of acute COVID-19. It is difficult to know what proportion of these patients went on to develop long COVID; the recent introduction of ICD-10 codes for long COVID 9 may enable studies on this topic in the future.…”
Section: Risk Of New-onset Psychiatric Sequelae Of Covid-19 In the Ea...mentioning
confidence: 99%
“…Our study did not focus specifically on long COVID, but instead investigated a cohort of patients following a diagnosis of acute COVID-19. It is difficult to know what proportion of these patients went on to develop long COVID; the recent introduction of ICD-10 codes for long COVID 9 may enable studies on this topic in the future.…”
Section: Risk Of New-onset Psychiatric Sequelae Of Covid-19 In the Ea...mentioning
confidence: 99%
“…Also, since the use of the code began only recently, patients with long COVID that were diagnosed prior to the introduction of the code are not included, limiting our ability to compare the current clinical manifestations with those observed earlier in the pandemic before widespread vaccination and with different distributions of SARS-CoV2 strains and variants. However, in a pilot study in Denmark, coding with U09.9 was found to have a positive predictive value of 94% for long COVID (56) .…”
Section: Discussionmentioning
confidence: 98%
“…However, in a pilot study in Denmark, coding with U09.9 was found to have a positive predictive value of 94% for long COVID. 56 Our ability to capture clinical manifestations of long COVID is limited by the accessibility of clinical data in EHR systems. Of the 287 HPO terms we identified as being used in published cohort studies on long COVID, 19 only 116 were identified in our data.…”
Section: Study Limitationsmentioning
confidence: 99%
“…In this perspective, brain fog would be one of the symptoms of this broader syndrome, best for cognitive aspects. On the other hand, several studies treat fatigue and brain fog as distinct post-infection sequelae, although frequently occurring together [ 2 , 13 , 25 , 26 ]. The former would involve mainly a sort of physical asthenia, while the latter would be characterized primarily by an excessive easiness to cognitive weakness.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, brain fog and forms of cognitive impairment would substantially overlap [ 4 , 6 , 14 , 17 , 23 ]. On the other hand, several studies keep brain fog, and cognitive deficits separate, suggesting that they represent two distinct clinical entities [ 7 , 9 , 10 , 13 , 16 , 26 , 28 , 29 ]. Despite this, data on their co-occurrence are lacking.…”
Section: Introductionmentioning
confidence: 99%